(untitled) (Economics and region, 2022)
The present determines the important role of availability and sufficiency of funds for the functioning of domestic enterprises. The financial and economic crisis caused by the state of war in Ukraine creates new challenges for enterprises, requires the improvement of management and planning technologies, forces to solve the issue of directing cash flows to the most urgent areas of activity. The article is devoted to highlighting the problems of enterprise cash budgeting, summarizing approaches, methods and modern budgeting tools in the system of cash flow management and management accounting. The need to transform the budgeting system based on the use of optimization blocks and modern information technologies are substantiated. The transformation of budgeting algorithms is caused by the need to ensure the efficiency of the enterprise in the conditions of influence of external risks and martial law. The traditional budgeting process should be supplemented with optimization blocks at each of its main stages, which provides a multivariate approach to managerial decision making, search for alternative options and directions of development of the enterprise, taking into account the influence of external and internal factors. This will allow timely and quickly to influence changes (risks), deviations, and achieve the strategic goals of the enterprise. The result of the planned methodological approach of optimization of the budgeting system is the budget of funds of the enterprise. The tasks of the enterprise’s cash flow budgeting system are also defined. Recommendations have been made that will help increase the effectiveness of cash flow management, in particular, budgeting in crisis conditions. The relevance is due to the fact that in the period of crisis transformations, the problems of ensuring a sufficient level of life activity of enterprises acquire special importance.